2018
DOI: 10.1130/l746.1
|View full text |Cite
|
Sign up to set email alerts
|

Late Miocene rejuvenation of central Idaho landscape evolution: A case for surface processes driven by plume-lithosphere interaction

Abstract: We utilized field measurements of erosion rates and topographic analyses to constrain the timing and magnitude of landscape rejuvenation on the western flank of the Rocky Mountains in central Idaho, United States. Deeply incised canyons of the Clearwater, Salmon, and Snake Rivers dissect a broad region of roughly 8 × 10 4 km 2 . Along the Salmon River, an observable break in slope separates relict landscapes of low relief (<400 m valley depth) from high-relief landscapes (1200-1600 m valley depth) adjusting to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Beranek et al () show this capture occurring near the confluence between the Salmon and North Fork Salmon Rivers sometime between 4 and 2 Ma (Figures and in Beranek et al, ). Based on the sharp westward turn in the Salmon River near this confluence (NF Salmon in Figure a), Anderson () similarly suggested that this sharp turn was caused by drainage capture “by headward erosion of a vigorous stream from the west.” Although Anderson's hypothesis is qualitative, it is possible this western stream's vigor was caused by the rock‐uplift variations proposed by Larimer et al (). Much like the drainage capture scenarios we consider (Figure ), drainage capture along the upper Salmon River would cause incision that decreases downstream.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Beranek et al () show this capture occurring near the confluence between the Salmon and North Fork Salmon Rivers sometime between 4 and 2 Ma (Figures and in Beranek et al, ). Based on the sharp westward turn in the Salmon River near this confluence (NF Salmon in Figure a), Anderson () similarly suggested that this sharp turn was caused by drainage capture “by headward erosion of a vigorous stream from the west.” Although Anderson's hypothesis is qualitative, it is possible this western stream's vigor was caused by the rock‐uplift variations proposed by Larimer et al (). Much like the drainage capture scenarios we consider (Figure ), drainage capture along the upper Salmon River would cause incision that decreases downstream.…”
Section: Discussionmentioning
confidence: 96%
“…An increase in rock uplift could be achieved through a range of alternative drivers, however. One possibility is that flexural isostasy is ongoing due to the region's suspected lithospheric loss (Camp & Hanan, ; Darold & Humphreys, ; Hales et al, ), as proposed by Larimer et al (). These authors also modeled the flexure of an elastic plate subjected to a buoyant load to demonstrate that density changes extending 200 km north of the Snake River Plain could cause the proposed northward surface tilting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations